2017
DOI: 10.1038/s41598-017-03310-x
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase-4 and Adolescent Idiopathic Scoliosis: Expression in Osteoblasts

Abstract: It has been proposed that girls with adolescent idiopathic scoliosis (AIS) tend to have a taller stature and a lower body mass index. Energy homeostasis, that is known to affect bone growth, could contribute to these characteristics. In circulation, dipeptidyl peptidase-4 (DPP-4) inactivates glucagon-like peptide-1 (GLP-1), an incretin that promotes insulin secretion and sensitivity. Our objectives were to investigate DPP-4 status in plasma and in osteoblasts of AIS subjects and controls and to evaluate the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…As documented in earlier literatures, abnormal metabolism has been implicated in the etiology of AIS. To characterize the role of DPP-4 in the metabolism of AIS patients, Normand et al [ 14 ] firstly isolated osteoblast from AIS patients and controls and reported abnormally down-regulated expression of DPP-4 in AIS patients. In the current study, we successfully validated that AIS subjects had remarkably lower DPP-4 expression in both serum and paraspinal muscles when compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As documented in earlier literatures, abnormal metabolism has been implicated in the etiology of AIS. To characterize the role of DPP-4 in the metabolism of AIS patients, Normand et al [ 14 ] firstly isolated osteoblast from AIS patients and controls and reported abnormally down-regulated expression of DPP-4 in AIS patients. In the current study, we successfully validated that AIS subjects had remarkably lower DPP-4 expression in both serum and paraspinal muscles when compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
“…DPP-4 inhibitor, launched and wildly used in clinical practice, was proven to improve BMD and decrease the risk of fracture in type 2 diabetes, establishing a relationship between DPP-4 and bone quality [ 13 ]. Normand et al [ 14 ] observed lower serum expression of DPP-4 in AIS patients. Moreover, remarkable differences in DPP-4 activity and regulation between osteoblasts of AIS patients and healthy controls were found in their study.…”
Section: Introductionmentioning
confidence: 99%
“…GLP-1 increases insulin release in the pancreas, enhancing insulin response with bone growth during adolescent development. This further explains the increased prevalence of AIS in individuals with lower BMI values [43,44].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Melatonin binds to melatonin receptors that are coupled to Gαi proteins and blocks the synthesis of cAMP produced by adenylate cyclases. We hypothesized that Gαi protein impairment could explain the melatonin-signaling pathway dysfunction 10 and other neuroendocrine abnormalities observed in AIS 1113 . We tested Gi-coupled receptor signaling using peripheral blood mononuclear cells (PBMCs) of AIS patients using cellular dielectric spectroscopy (CDS) 14 .…”
Section: Introductionmentioning
confidence: 99%